Vindhya Pradesh Second Five Year Plan Revised Volume II - Planning Commission (Planning Commission, 1955)
29 minor schemes costing about Rs. 67.8 lacs were proposed in the 1st plan. These schemes are proposed to irrigate about 45500 acres when fully matured. Out of the above 29 schemes, 13 schemes vide appendix will spill over to 2nd plan and it is proposed to spend about Rs. 23, 26,500/-over them to complete them. Out of the above 13 schemes work is already in progress on most of them. Remaining few like Goghri, Singpur canal, where work is not yet started, on be started very soon. All the above 13 schemes are proposed to be completed in the 1st year of the plan and the area benefitted will be about 26500 acres.
Government of Vindhya Pradesh
Public Works Department Vindhya Pradesh
Keywords: Minor schemes; Major Irrigation schemes; Cottage and Small Industries; Education Department; Conversion of Basic classes; Lady Teachers Quarters; Technical Education; Junior Technical Schools; University Education; Social Education; Primary Education; Tanning of Teachers